Measuring systemic risk in the global banking sector: A cross-quantilogram network approach - Eduard Baumöhl; Elie Bouri; Thi-Hong-Van Hoang; Syed Jawad Hussain Shahzad; Tomáš Výrost (Economic Modelling, 2022)
We propose a new systemic risk index based on the interdependence of extreme downside movements of stock returns using the cross-quantilogram and network analysis approach. While quantile dependence allows for sensitivity in times of market downturn, the topological network properties allow for capturing the interconnectedness of the banking system and identification of the specific contribution of each individual bank. Using this design, the proposed systemic risk index is not only easy to calculate and interpret but identifies the banking system's significant transmitters and receivers of extreme downside risk. For the empirical evaluation of the proposed risk index, we use a sample of 83 large banks during the 2003-2020 period, spanning multiple recent crises affecting the banking market. The proposed index is found to be robust in comparison to major alternative systemic risk measures.
Keywords: G01; G21; 330; Systemic risk; Downturn interdependence; Network; Cross-quantilograms; Global banks; COVID-19 pandemic